Analgesic efficacy of diazepam and placebo in patients with temporomandibular disorders: A double blind randomized clinical trial - G V Pramod; P Shambulingappa; M C Shashikanth; Shailesh Lele (Indian Journal of Dental Research, 2011)
Aim: The aim of the study was to evaluate and compare the analgesic efficacy of placebo and diazepam in patients with temporomandibular disorder. Materials and Methods: Thirty-five patients were recruited with a diagnosis of temporomandibular disorder based on standard clinical diagnostic criteria for temporomandibular disorder. The patients were put in to one of the two groups: placebo or diazepam at random. The average pain intensity was recorded with visual analog scale (VAS) at pretreatment, at weekly interval till the completion of a three-week trial and at post-treatment visit on the eighth week from baseline. The secondary outcome measures were changes in masticatory muscle tenderness, viz. massater muscle, lateral pterygoid muscle, medial pterygoid muscle and temporalis muscle and changes in mouth opening. Statistical Analysis: Intra-group comparison for analgesic efficacy and mouth opening was carried out by Wilcoxon′s signed ranked test. Inter-group comparison for analgesic efficacy was also carried out using Mann-Whitney′s test. Results: A statistically significant (P<0.01) decrease in temporomandibular disorder pain in the placebo group (65%) and statistically highly significant (P<0.001) decrease in the diazepam group (72%) were observed on VAS after three weeks of treatment. The inter-group comparison demonstrated no statistically significant difference between the groups. Conclusion: This study suggests that the placebo can give near similar results as diazepam can. So the role of placebo should also be considered as one of the important management strategies. In the short term, reduction in the masticatory muscle tenderness and significant improvement in the mouth opening in both the groups were observed.